How does finishing duration on lucerne pasture influence the muscle and fat spectro-colorimetric properties and dorsal fat firmness in lambs? - S. Prache; B. Graulet; L. Rey-Cadilhac (Animal, 2024)
There are a number of differences in the meat and carcass quality traits between pasture-raised and concentrate-raised lambs that may further be used to trace back the diet, but the extent to which these differences are modulated by pasture-finishing duration is unknown. In this study, we investigated the changes in longissimus thoracis et lumborum muscle and fat spectrocolorimetric properties, and dorsal fat firmness, in lambs switched from a stall-fed concentrate-based diet to grazing on lucerne for various durations (0, 21, 42, 63 days) pre-slaughter. Stall-fed lambs from the different treatment groups were managed in a single group and lucerne pasture-finished lambs from the different treatment groups also co-grazed in a single group. The level of concentrate fed to stall-fed lambs was adjusted to maintain a similar mean pattern of growth between lucerne pasture-fed and stall-fed lambs. The trial used a total of 141 lambs over two successive years. Dorsal fat was firmer in lambs finished on lucerne pasture, even for the shortest finishing duration (21 days), the difference being of commercial importance. Dorsal fat colour and carotenoid content showed changes at 21 days on lucerne pasture but did not change further for longer lucerne pasture-finishing durations. In contrast, perirenal fat lightness, yellowness, chroma and carotenoid content showed changes at 21 days on lucerne pasture and increased consistently with lucerne pasture-finishing duration. Although these changes in fat spectrocolorimetric properties were not, or barely, visible to the naked eye, they could be of interest for authenticating the duration of lucerne pasture-finishing. Muscle redness increased consistently with the duration of lucerne pasture-finishing, the change becoming significant from 42 days on lucerne pasture and being visible to the naked eye. We observed a consistent decrease in muscle hue angle and perirenal fat redness and a consistent increase in perirenal fat hue angle with lucerne pasture-finishing duration, but these changes only became significant from 63 days on lucerne pasture. The pattern of change in the lamb carcass and meat quality traits measured according to lucerne pasture-finishing duration therefore varied between the tissues and quality traits.